The impact of a changed writing environment on students' motivation to write - Myhill, Debra; Cremin, Teresa; Oliver, Lucy (Frontiers in Psychology, 2023)
The act of writing is widely acknowledged to be a complex and challenging activity, and in parallel, we know that student motivation to write is a predictor of writing performance. So understanding what characteristics of the writing classroom support or foster motivation remains a salient concern. Research has shown that UK teachers are more likely to see themselves as readers than writers, which may affect how they teach writing. This paper reports on student focus group interview data from a study which sought to strengthen teachers' sense of themselves as writers, and to examine the impact of this on students' classroom experience of writing and their writing outcomes. The participant teachers experienced a creative writing residential, which established a writing community led by two professional writers, with the goal of changing teachers' professional practice in their own writing classrooms. The study was mixed methods, comprising a randomised controlled trial and a comprehensive qualitative dataset collating data from both the residential and the classroom. This paper presents the qualitative analysis of 32 interviews with 16 student focus groups, exploring their responses to their teachers' changed practices and how it connected with their motivation to write. The interview analysis shows how many students responded positively to new teaching practices which gave them greater autonomy and choice, and established a more collaborative way of working. This led to increased confidence in and motivation to write. The study highlights the importance of the classroom environment in supporting and sustaining motivation to write, and underlines that motivation is not simply an internal characteristic of an individual but is situated within the context of a community of writers.